IMPLEMENTASI APLIKASI AREK SUROBOYO SIAP KERJO (ASSIK) PADA DINAS PERINDUSTRIAN DAN TENAGA KERJA KOTA SURABAYA - Jihan Salsabillah Anaqoh; Kalvin Edo Wahyudi (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to describe the implementation of the Arek Suroboyo Siap Kerjo (ASSiK) application at the Department of Industry and Labor in the City of Surabaya. The method used is qualitative with descriptive purposes. Data collection techniques used include observation, interviews, and documentation. The theory used is the theory of Van Meter and Van Horn about six indicators of successful policy implementation. The results of the study show that: (1) standards and objectives are not good; (2) resources are not good; (3) communication is not good; (4) the characteristics of implementing agents are good; (5) social, economic, and political conditions are good; and (6) the disposition is good. Based on the results of the study, it can be concluded that the implementation of the Arek Suroboyo Siap Kerjo (ASSiK) application at the Surabaya City Industry and Labor Service is quite good.